THE ROAD TO MINAHASA: THE EARLY ARRIVAL AND TRADITIONS OF BANTEN MUSLIMS IN TOMOHON'S JAVANESE VILLAGE - Eka Yuliana Rahman (Aqlam: Journal of Islam and Plurality, 2023)
Abstract: The research on the early arrival of the Muslim community in Tomohon Javanese Village (Kampung Jawa Tomohon) has its own story, unlike the Muslim community in Kampung Jawa Tondano Minahasa, which was pioneered by Kiyai Mojo and his followers in 1829. In the Tomohon area, Islam was allegedly introduced by several people from the sultanate of Banten. This research aims to investigate how the early arrival of Banten Muslims introduced Islam in Tomohon. This research uncovered the story of who and how the Banten Muslims first arrived. Method of research using observation, document study and in-depth interviews with key informants. This research found that Tubagus Buang was a pioneer also as the leader of the first group of Banten Muslims to arrive in Tomohon Minahasa. He was a mysterious figure. Tubagus Buang's grave is still believed by the residents of Sarongsong Javanese village to be in their area, namely Kalapa Empat. In the Sarongsong District they settled in the Kayu Payung area. For a long time in the area they chose to procreate through marriage with Minahasa women. In addition, the typical Islamic traditions in Tomohon Javanese Village come from the tariqat tradition inherited from Banten, such as the Lebaran Ketupat celebration and Rudat art. There has not been much writing on the history of Tomohon Javanese Village.Key Words : Kampung Jawa Tomohon, Tubagus Buang, Minahasa MuslimsAbstrak: Penelitian mengenai awal mula kedatangan komunitas Muslim di Kampung Jawa Tomohon memiliki cerita tersendiri, berbeda dengan komunitas Muslim di Kampung Jawa Tondano Minahasa yang dipelopori oleh Kiyai Mojo dan para pengikutnya pada tahun 1829. Di daerah Tomohon, Islam diduga diperkenalkan oleh beberapa orang dari kesultanan Banten. Penelitian ini bertujuan untuk mengetahui bagaimana awal mula kedatangan Muslim Banten memperkenalkan Islam di Tomohon. Penelitian ini mengungkap kisah tentang siapa dan bagaimana Muslim Banten pertama kali datang. Metode penelitian menggunakan observasi, studi dokumen dan wawancara mendalam dengan narasumber. Penelitian ini menemukan bahwa Tubagus Buang adalah seorang perintis sekaligus pemimpin kelompok pertama Muslim Banten yang tiba di Tomohon Minahasa. Ia adalah sosok yang misterius. Makam Tubagus Buang masih diyakini oleh warga kampung Jawa Sarongsong berada di wilayah mereka, yaitu Kalapa Empat. Di Kecamatan Sarongsong mereka bermukim di daerah Kayu Payung. Sejak lama di daerah tersebut mereka memilih beranak pinak melalui pernikahan dengan perempuan Minahasa. Selain itu, tradisi Islam yang khas di Kampung Jawa Tomohon berasal dari tradisi tarekat yang diwarisi dari Banten, seperti perayaan Lebaran Ketupat dan kesenian Rudat. Saat ini belum banyak tulisan yang membahas tentang sejarah Kampung Jawa TomohonKata Kunci: Kampung Jawa Tomohon, Tubagus Buang, Minahasa Muslim